Determinan Kepatuhan Membayar Pajak Bumi Dan Bangunan Di Kecamatan Cluring, Kabupaten Banyuwangi - Devi Indah Permatasari; Muhaimin Dimyati; Nanda Widaninggar (JAKUMA : JURNAL AKUNTANSI DAN MANAJEMEN KEUANGAN, 2022)
Taxes are one of the sources of national development costs to improve people's welfare. This study aims to analyze whether Socialization, Tax Knowledge, Tax Sanctions, Taxpayer Awareness, and Service Quality have a simultaneous and partial effect on Compliance with Paying Land and Building Taxes in Cluring Sub-District, Banyuwangi District. By a hundred of respondents, the analytical technique used in this research is multiple linear regression. The results showed that Socialization, Tax Knowledge and Service Quality had a positive not significant effect on Land and Building Taxpayer Compliance. Meanwhile, Tax Sanctions and Taxpayer Awareness had a positive and significant impact on Land and Building Taxpayer Compliance in Cluring District, Banyuwangi Regency.